2006
DOI: 10.1002/neu.20313
|View full text |Cite
|
Sign up to set email alerts
|

Down‐regulation of torp4a, encoding the Drosophila homologue of torsinA, results in increased neuronal degeneration

Abstract: Early-onset torsion dystonia is a dominant motor disorder linked to mutations in torsinA. TorsinA is weakly related to a superfamily of chaperone-like proteins. The function of the torsin group remains largely unknown. Here we use RNAi and over-expression to analyze the function of torp4a, the only Drosophila torsin. Targeted down-regulation in the eye causes progressive degeneration of the retina. Conversely, over-expression of torp4a protects from age-related degeneration. In the retinas of young animals, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 64 publications
3
26
0
Order By: Relevance
“…5). Thus, these results support the earlier identification of Punch, as a dtorsininteracting gene [87]. Subsequent interaction experiments demonstrated that torsin -/+ ; ple -/+ mutants, doubly heterozygous for dtorsin and tyrosine hydroxylase, respectively, displayed a mildly enhanced locomotion phenotype, while heterozygous Punch mutations strongly enhanced mobility deficits in combination with the heterozygous torsin knock-out mutation.…”
Section: Drosophila Models Of Dyt1 Dystoniasupporting
confidence: 74%
See 2 more Smart Citations
“…5). Thus, these results support the earlier identification of Punch, as a dtorsininteracting gene [87]. Subsequent interaction experiments demonstrated that torsin -/+ ; ple -/+ mutants, doubly heterozygous for dtorsin and tyrosine hydroxylase, respectively, displayed a mildly enhanced locomotion phenotype, while heterozygous Punch mutations strongly enhanced mobility deficits in combination with the heterozygous torsin knock-out mutation.…”
Section: Drosophila Models Of Dyt1 Dystoniasupporting
confidence: 74%
“…Further analysis revealed that dopaminergic neurons were present in mutant brains and expressed tyrosine hydroxylase, the first and rate-limiting enzyme in dopamine biosynthesis. Thus, unlike RNAi knock-down of dtorsin in the fly eye [87], neural degeneration in torsin-deficient CNS was not evident. Nevertheless, DA pools in hemizygous males and heterozygous females were strongly reduced, which could be due to diminished synthesis of, or increased turnover of, this catecholamine.…”
Section: Drosophila Models Of Dyt1 Dystoniamentioning
confidence: 99%
See 1 more Smart Citation
“…One hypothesis is that torsinA may have a chaperone-like function (44,45), regulating the folding of proteins involved in SV trafficking, such us snapin. Interestingly, torsinA displays sequence homology with N-ethylmaleimide-sensitive fusion protein (5), an AAA-ATPase essential for neurosecretion that is responsible for SNARE recycling (46).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a neuroprotective role for torsins is further suggested by a report in flies, where targeted RNAi knockdown of torp4a, the only Drosophila torsinA homolog, causes progressive retinal degeneration (Muraro and Moffat, 2006). In this regard, the enhancement of native WT torsinA function may not only serve to overcome the neuronal deficit of mutant torsinA-associated EOTD, but might also be of benefit to the treatment of diseases resulting from defects in processing mutant proteins (e.g.…”
Section: Discussionmentioning
confidence: 99%